Mild depressive symptoms, self-reported disability, and slowing across multiple functional domains - Albert, Steven M.; Bear-Lehman, Jane; Burkhardt, Ann (International psychogeriatrics, 2012)
Background: Subthreshold depressive symptoms are common in older adults. The threshold for the clinical significance of such symptoms is unclear. Mechanisms linking depressed mood to increased risk of disability need further investigation. Methods: Among older adults who did not meet criteria for depression, respondents reporting no anhedonia and dysphoria over the past two weeks were compared to respondents reporting occasional symptoms with respect to self-reported disability and cognitive, psychomotor, and physical performance tests. Results: Of 312 community-resident participants without dementia, 35.3% (n = 110) reported one or both of the two depressive symptoms at mild severity (no more than “several days” in the past two weeks). Older adults with mild depressive symptoms reported more physician-diagnosed medical conditions (2.2 vs. 1.8, p < 0.01) and mobility problems (3.0 vs. 1.8, 0–7 scale, p < 0.001), and were slower in gait (0.80 vs. 0.73 m/sec, p < 0.01) and speed of cognitive processing (Trail B, 166.1 vs. 184.7 sec, p < 0.001). In regression models that adjusted for sociodemographic and medical status, subthreshold symptoms were not a significant correlate of slowing in gait speed or cognitive performance. However, subthreshold depressive symptoms were associated with self-reported mobility limitation in models that adjusted for observed performance. Conclusions: Mild depressive symptoms in this sample were not an independent correlate of slowed performance. However, the presence of mild depressive symptoms was associated with poorer appraisal of mobility after adjustment for objective measures of mobility.